A Model of Revitalization at Pajak Ikan Lama, Medan - Dwi Lindarto Hadinugroho; M. Ricky Alamsyah S (Talenta Publisher, 2018)
Revitalization is an effort to reproduce the values of an area that was once vital, but due to some reasons, it experienced degradation. This research discusses Pajak Ikan Lama as a revitalization area. There are two parts of scale in revitalization, namely macro level and micro level. Revitalization process in a neighborhood includes improvement of physical, economic, and social aspects. To undergo a revitalization, Pajak Ikan Lama needs improvement as well. The physical aesthetic of the area does not stand as the only solution to address this issue. It needs a series of equipment, with an escalation of the economy for the people as well as a recognition for the cultural value. This research used the qualitative method, also known as an artistic method because the process is emphasized in art, less patterned, and more likely to be interpretative. The collected data from the field is processed using interpretation. The result of this research found that most of the effort needed to revitalize the area lay on physical rearrangement, such as pedestrian, roadblock, welcome gate, street furniture, and street market.